The Limits of Industrialization in Post-Orde Baru Indonesia: State-Corporatism and Technological Inferiority - Margiansyah, Defbry (RMPI-BRIN, 2017)
As competitiveness gains currency, it compels many governments’ concerns in achieving economic resilience to avoid the Middle-income Trap. Indonesia has focused on promoting industrialization and economic diversification as a response to the probability of being trapped. However, it has been shown that the performance of the manufacturing sector in Indonesia has been unsatisfying due to the inability to enhance human and technological competences and managing the transition from labor- and resource-intensive to capital- and technology-intensive industries. This situation signifies the importance of industrial revitalization in Indonesia by strengthening the weakest links, innovation, and human capital through the adoption of capability-focused industrial policy on innovation and technology. This paper examines factors that challenge Indonesia to develop innovation and technological capabilities in the industrial sector and analyze the role of the state in organizing industrial policy based on the adoption of the capabilities-focused strategy within reindustrialization in the democratic setting. Employing Thee Kian Wie’s conditions for industrial technology development and Dani Rodrik’s industrial policy, this study reveals vital factors challenging Indonesia’s efforts on innovation and technological development in manufacturing industries. It also found two ideational factors that affect the Orde-Baru bureaucratic culture and practice remain intact in the policy formulation and implementation, and ultimately obstructing current industrial policy to achieve the policy goals and right institutional setting.